Neurogenic tumors and tumor-like lesions of the oral and maxillofacial region: A clinicopathological study - Ohoud Alotaibi; Manal Al Sheddi (Saudi Dental Journal)
Objective: Oral and maxillofacial lesions of neural origin are rare soft tissue neoplasms. The aim of the present study is to review the epidemiological data of oral and maxillofacial neurogenic lesions submitted for diagnosis to our laboratory over a 31-year period (August 1984–March 2015). Materials and methods: The available formalin-fixed embedded specimens, Hematoxylin and Eosin slides, demographic and clinical data were retrieved. Results: Thirty-one cases were included in this study, representing 0.6% of the 5161 biopsies submitted. Most of the diagnosed cases 11 (35.5%) were traumatic neuromas. The other cases included 2 (6.5%) solitary circumscribed neuromas, 2 (6.5%) melanotic neuroectodermal tumors of infancy, 2 (6.5%) Schwannomas, 5 (16.1%) granular cell tumors, and 9 (29%) neurofibromas. The patients’ ages ranged from 5 months to 78 years. Among these cases, 16 were males (51.61%) and 15 were females (48.38%). Conclusion: This analysis showed that neural lesions affecting the oral and maxillofacial region were rare and mostly benign in nature. Such lesions should be carefully diagnosed because of their association with life-threatening syndromes and the possibility of malignant transformation. Keywords: Neural, Nerve sheath neoplasms, Neuroma, Neurofibroma, Schwannomas, Oral